P–128 Audit of testicular sperm in assisted conception for non-azoospermic infertile couples. (6th August 2021) - Merrett, C; Schlager, D; Yasmin, E; Seshadri, S; Serhal, P; Ralph, D; Sangster, P
Abstract: Study question: What live birth rate do we see when we use testicular sperm in ART for non-azoospermic couples after at least one previous failed cycle? Summary answer: In our cohort of couples 24% had a live birth using testicular sperm and therefore was not higher than national average ART rates. What is known already: There is increased interest in using testicular sperm in assisted reproduction technology (ART) to improve outcomes after previous failed cycles. Mehta et al. reported results of a 50% live birth rate using testicular sperm in the first cycle for couples with oligospermia and a history of failed cycles with ejaculated sperm. We aim to audit our results in a similar population of couples. Study design, size, duration: St Peters Andrology Centre in London, United Kingdom completed 128 surgical testicular sperm retrievals reviewed between the two-year period of 2018–2019. We conducted a retrospective audit of their paper-based records to identify those couples with injectable sperm on their semen analysis and who had previous cycles attempts using ejaculated sperm. Participants/materials, setting, methods: We identified 27 couples who underwent testicular sperm extraction despite having an ejaculated semen analysis with injectable sperm and at least one previous failed cycle. A systematic review of their paper and electronic medical record was conducted to assess live birth rates and fertilization rates from ART. Main results and the role of chance: Couples had an average male age of 41 (range 31–60) and an average female age of 38 (range 30–45). The men had an average serum testosterone of 15 nmol/L (range 8–35 nmol/L) and an average serum FSH of 8.9 IU/L (range 1.7–30 IU/L). 59% (n = 17) of men had a DNA fragmentation index completed with an average score of 41% (range 31%–51[Y1]%). In the women the mean serum anti-Müllerian hormone (AMH) was 15.8 pmol/l (range 1–64 pmol/l). With ejaculated sperm the fertilization rate was 59% (95% CI [27%, 59%]) and blastocyst conversion rate was 43% (95% CI [50%, 69%]). There was no statistical significance with testicular sperm where the fertilization rate was 58% (95% CI [51%, 65%]) and blastocyst conversion rate was 54% (95% CI [40%, 67%]). Overall, there were 7 clinical pregnancies in this population of couples. Of these clinical pregnancies, 2 miscarried and 5 progressed to a live birth. This audit yielded a live birth rate per cycle of 15% and a live birth rate per couple of 24%. Limitations, reasons for caution: Limitations of the study are low number of patients and absence of a control group. Wider implications of the findings: We recommend caution and further analysis going forward using testicular sperm in ART where ejaculated sperm in available. Trial registration number: Not applicable